NAVIGATING LINGUISTIC AND CULTURAL LANDSCAPES IN LITERARY TRANSLATION FROM UZBEK TO ENGLISH (Лучшие интеллектуальные исследования, 2025)
Annotation: This article explores the multifaceted challenges and rewards inherent in the literary translation process between Uzbek and English. It delves into the significant linguistic and cultural disparities that translators must navigate to faithfully render the nuances of Uzbek literature for an English-speaking audience. The discussion encompasses issues of lexical equivalence, grammatical structures, cultural context, stylistic variations, and the crucial role of the translator as a cultural mediator. Ultimately, the article highlights the importance of nuanced and culturally sensitive translation in fostering cross-cultural understanding and appreciation of Uzbek literary heritage.